HUBUNGAN ANTARA KADAR ZINK (Zn) SERUM DENGAN ERITEMA NODOSUM LEPROSUM (ENL) PADA LEPRA TIPE BL/LL - , Sri Agustina S ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The study was aimed to investigate the difference between mean of serum zinc level in ENL and non ENL, the correlation between serum zinc level and Erythema Nodosum Leprosum (ENL) among BL/LL type of leprosy patients. Methods: A cross sectional design was used in this study. Patient of BL and LL of leprosy with ENL and without ENL were recruited in this study. Diagnosis of leprosy was established by clinical, bacterioscopis and histopathological examination, whereas ENL was confirmed clinically by systemic symptoms as eritematous nodules on the face, arm and lower legs. ENL score was calculated according to van Braekel. The serum zinc level was measured by Atomic Absorption Spectrophotometer (AAS) method. The difference of serum zinc level in patient with ENL and those without ENL was analyzed by using Mann Whitney test with significant level at P < 0,05. The correlation between the serum zinc level and ENL score was analyzed by using Pearson correlation test with significant level at P <0,05. Results: Fifty-two subject met the inclusion criteria, divided into two groups, 28 with ENL and 24 without ENL. The result showed that mean of serum zinc level in ENL was 36,84Â±15,59 Î¼g/dL compared to 44,64Â±16,45 Î¼g/dL in those without ENL (P>0,05). The correlation between serum zinc level and ENL score not significant (r= -0,17). The mean of bacterial index (BI) in ENL was 3,8+ compared to 3,4+ in those without ENL (P<0,05). And the correlation of zinc serum level and BI in ENL (r= -0,39 and P=0,04) and non ENL (r = - 0,51 and P=0.01). Conclusion: Mean of serum zinc level in patient with ENL was lower compared to those of non-ENL although statistically not significant difference. There is also no correlation between serum zinc level and ENL score. Significant difference was found on the mean of BI in ENL compared to non ENL, and also negative correlation between serum zinc level and BI in ENL and non ENL.